2017
DOI: 10.1053/j.gastro.2017.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Use of Monitored Anesthesia Care for Outpatient Gastrointestinal Endoscopy in a Capitated Payment System

Abstract: Background & Aims Use of monitored anesthesia care (MAC) for gastrointestinal endoscopy has increased in the Veterans Health Administration (VHA), as in fee-for-service environments, despite the absence of financial incentives. We investigated factors associated with use of MAC in an integrated healthcare delivery system with a capitated payment model. Methods We performed a retrospective cohort study using multi-level logistic regression, with MAC use modeled as a function of procedure year, patient- and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
(32 reference statements)
1
11
0
Order By: Relevance
“…Previous studies have consistently found that anesthesia use during outpatient colonoscopy varies significantly by region of the country, and the Northeast has been the region with the highest use of AA in many of these studies. [2][3][4][5]8,12 We also found this significant variation in anesthesia use by region, though the South was found to have a higher proportion of AA during outpatient colonoscopy as compared with the Northeast. This conflicting finding may be secondary to a potentially higher representation of the state of Florida in the sample of southern hospitals in the Perspective database, as multiple prior studies have found rates of AA use in Florida to be similar to those in the Northeast.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies have consistently found that anesthesia use during outpatient colonoscopy varies significantly by region of the country, and the Northeast has been the region with the highest use of AA in many of these studies. [2][3][4][5]8,12 We also found this significant variation in anesthesia use by region, though the South was found to have a higher proportion of AA during outpatient colonoscopy as compared with the Northeast. This conflicting finding may be secondary to a potentially higher representation of the state of Florida in the sample of southern hospitals in the Perspective database, as multiple prior studies have found rates of AA use in Florida to be similar to those in the Northeast.…”
Section: Discussionsupporting
confidence: 56%
“…In addition to being associated with increased cost, [2][3][4] this widespread practice has been associated with a possible increase in overall complication rates, 5,6 including aspiration pneumonia risk, 6,7 without being shown to increase overall colonoscopy quality indicators such as adenoma detection [8][9][10] and cecal intubation rates. 10,11 Previous studies have assessed various geographic, patient-related, and facility-related predictors of the use of AA using claims data from commercial insurers and Medicare, [2][3][4][5][6]8,12 but data on hospital-based endoscopy, which have represented between 19% and 57% of screening colonoscopies in the Medicare population in prior analyses, 2,6 have been limited. In these prior studies, use of AA has generally been found to be highest in the Northeast compared with other regions in the United States, but results on patient-related factors such as age and race have been mixed.…”
mentioning
confidence: 99%
“…Traditionally, benzodiazepines have been used as the ondemand sedative. 37 In our endoscopic unit, we usually have two nurse anesthetists supervised by one anesthesiologist, who readily administered propofol when needed. Propofol has a rapid onset (< 1 min), which comes in handy for patients suffering from pain during colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of its narrow therapeutic window, an anesthesia specialist is usually required to administer it. 37 In our endoscopic unit, we usually have two nurse anesthetists supervised by one anesthesiologist, who readily administered propofol when needed. In settings without the presence of an anesthesia specialist, endoscopist-directed propofol sedation might be a feasible alternative, 38 given the low dose of propofol required by on-demand sedation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies of AA use in integrated health care delivery systems showing increased utilization even in the absence of economic incentives suggest that focusing solely on economic drivers may be misguided, and a more nuanced approach may be needed. 19 By focusing on developing more refined, evidence-based clinical criteria regarding which patients are most likely to benefit from AA, whether because they would not be sedated adequately with standard sedatives or because they would be at higher risk of procedural or sedation-related complications with standard sedation, we can advance the dialogue and help gastroenterologists to better demonstrate the value of the services they provide.…”
mentioning
confidence: 99%